Promoting physical activity for children with autism spectrum disorders during Coronavirus outbreak: Benefits, strategies, and examples - Yarımkaya, Erkan; Esentürk, Oğuz Kaan (International Journal of Developmental Disabilities, 2020)
Described as a global outbreak (pandemic) by the World Health Organization, Coronavirus disease (COVID-19) raises great concern with more than 2 million infected patients worldwide. A series of measures are taken by governments worldwide to prevent the spread of the outbreak. As new cases increase, people are asked to stay at home. Active living areas such as sports centers, parks and schools are closed in most countries. In this process, staying at home for a long time makes it difficult for individuals with special needs such as Autism Spectrum Disorders (ASD) to stay physically active as well as typically developing individuals. The education process of children with ASD is disrupted, especially due to closed special education schools and rehabilitation centers. Online learning environments are often not suitable for children with ASD. It is predicted that excessive weight, obesity and sedentary life, which are high in children with ASD, may increase even more due to COVID-19. This article outlines the benefits of physical activity for children with ASD and provides strategies and examples of physical activity for children with ASD during the COVID-19 outbreak. The article is thought to be a guide for encouraging children with ASD in the home environment to physical activity.
KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2020.1756115 2405685:4SKEKBD6
Keywords: COVID-19; children with ASD; physical activity; stay at home